2017
DOI: 10.15446/dyna.v84n203.56698
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy index for swine thermal comfort at nursery stage based on behavior

Abstract: This work aims to develop and test a computational mathematical model, based on the fuzzy set theory, to predict the rate of thermal comfort by means of the swine behavior in relation to their age and to the black globe humidity index for two nursery types. Nursery 1 had brick stalls with fully slatted metal flooring, and nursery 2 had wooden stalls with fully slatted plastic flooring. Nursery style 2 presented a higher frequency of behavior in the condition comfort than nursery style 1, respectively 39,32% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Curtis' successors continued this work. Here, James Pettigrew [26] found that pigs not only have their own preferences for temperature [27], but also try, if they are able, on the basis of trial and error, to master ways of "managing" the heating in a room [28]. Next, Sarah Boysen argued [23] that pigs are able to concentrate with an intensity higher than in the case of chimpanzees.…”
Section: Introduction To Pig Herd Optimizationmentioning
confidence: 99%
“…Curtis' successors continued this work. Here, James Pettigrew [26] found that pigs not only have their own preferences for temperature [27], but also try, if they are able, on the basis of trial and error, to master ways of "managing" the heating in a room [28]. Next, Sarah Boysen argued [23] that pigs are able to concentrate with an intensity higher than in the case of chimpanzees.…”
Section: Introduction To Pig Herd Optimizationmentioning
confidence: 99%
“…Además de exigirse en gran parte de las normativas internacionales, está también asociado a conceptos como economía circular y estrategias de carbono cero, las cuales privilegian las acciones/estrategias pasivas. Es de mencionar que el confort térmico se ha incluido también en algunos estudios en el sector agrícola (Damasceno et al, 2016;Freitas et al, 2017;Pareja Arcila et al, 2018) como mecanismo para mejorar las condiciones de animales en los gallineros, establos, etc. Temas que se salen del alcance de esta investigación.…”
Section: Estado De La Cuestionunclassified